Hydrogen sensing characteristics of Cu-PS-Si structures - Dzhafarov, TD; Omur, BC; Oruc, C; Allahverdiev, ZA (IOP PUBLISHING LTD, 2002)
The effect of ambient humidity on the current-voltage characteristics of Cu-PS (porous silicon) structures was investigated. The humidity-voltaic effect, i.e. generation of humid voltage (V-oc) in Cu-PS interface in humid atmosphere (up to 300 mV at 95% relative humidity) in dark and day-light illumination is discovered. Humidity-stimulated voltage generation is caused by the hydrogen component of water vapour of ambient. A possible mechanism of hydrogen-stimulated voltage generation in Cu-PS interface is suggested. Besides the effect of annealing in the range of 60-200degreesC in air on V-oc of Cu-PS structures was studied and decrease of values of V-oc depending on duration of annealing was discovered. These changes were attributed to diffusion of oxygen from air and oxidation of the copper film. (V-oc-t) data were used for estimation of the diffusion coefficients of oxygen in the Cu film. The temperature dependence of the oxygen diffusion coefficient in Cu films is described by the relation D = 5.2 x 10(-7) exp(-0.44/kT).
Keywords: POROUS SILICON; SENSOR; PHOTOLUMINESCENCE; WATER; Physics